ANTIBACTERIAL POTENCY OF CHITOSAN OLIGOMER PRODUCED BY Bacillus licheniformis MB-2 CHITOSANASE - Ekowati Chasanah; Meidina Meidina; Maggy T. Suhartono (Indonesian Fisheries Research Journal, 2008)
Bacillus licheniformis MB-2 chitosanase isolated from hot spring water in Manado, Indonesia, was used to produce chitosan oligomers.